Analisis Penjatuhan Pidana Penjara dan Pelatihan Kerja terhadap Anak Pelaku Tindak Pidana Menjadi Perantara dalam Jual Beli Narkotika - Kartadinata, Billiansyah; Fathonah, Rini; Triono, Agus (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Children are increasingly involved in narcotics crimes, not just as users but as intermediaries in drug transactions. This study examines the judicial reasoning behind the imposition of imprisonment and work training on a child offender in Decision No. 55/Pid.Sus-Anak/2024/PN.Tjk, and assesses whether such punishment aligns with the goals of juvenile sentencing. This normative legal research uses a statute and conceptual approach, supported by secondary data obtained from legal literature, which are analyzed qualitatively. The findings indicate that the court sentenced the child to two years of imprisonment at LPKA and two months of work training at LPKS. The decision was grounded on juridical considerations (violation of Article 114(1) of the Narcotics Law), philosophical justification (punishment as rehabilitation), and sociological factors (social impact and offender’s background). The punishment imposed reflects the purpose of juvenile justice, which prioritizes the child's reformation and reintegration rather than mere retribution. The ruling emphasizes the educational and preventive aspects of punishment, aiming to guide the child toward becoming a productive member of society.